KEANEKARAGAMAN DAN DOMINANSI ANGGREK ALAM DI HUTAN MANDU-MANDULA, TAMAN NASIONAL RAWA AOPA WATUMOHAI, SULAWESI TENGGARA - Mariana Zainun; La Panga Mpalasi; Alamsyah Flamin; Agus Setiawan; Muhammad Saleh Qadri; Baharuddin Dwi Isnanto (Jurnal Nusa Sylva, 2026)
Rawa Aopa Watumohai National Park (TNRAW) in Southeast Sulawesi is a strategic conservation area representing the Wallacea ecosystem with high floristic potential, yet baseline data on wild orchid diversity in this region remains severely limited. This study aims to identify species composition and analyze the community structure of wild orchids in Mandu-Mandula Forest, TNRAW, Southeast Sulawesi. The research was conducted from February to March 2025 in an area of approximately 47 ha using 100% exploration method with cruising technique and purposive sampling. Species identification was performed through comparative methods with taxonomic validation using Plants of the World Online (POWO) and World Flora Online (WFO). Data analysis included Importance Value Index (IVI) calculation for species dominance and Shannon-Wiener Diversity Index (H') for diversity levels. The results revealed 11 species of wild orchids, comprising 10 identified to species level and 1 to genus level (Dendrobium sp.), with a total of 920 individuals. Vandopsis lissochiloides (Gaudich.) Pfitz. showed absolute dominance with IVI of 76.85, while Dendrobium discolor Lindl. exhibited the lowest abundance (IVI = 3.27). The Shannon-Wiener diversity index yielded H' = 1.8956 (moderate category), yet the community structure demonstrated extreme inequality with absolute dominance by generalist species and rarity of specialist species. The high dominance of V. lissochiloides and low abundance of several other species indicate the need for in-situ conservation strategies prioritizing host tree protection, canopy microclimate stability, and regular population monitoring to prevent local extinction of vulnerable species in TNRAW.